Analisa Pemilihan Moda Transportasi Langsa – Medan Dengan Menggunakan Metode Analytical Hierarchy Process (AHP) - Yendi Naibaho; Nova Purnama Lisa; Wan Alamsyah (Universitas Medan Area, 2023)
When traveling from Langsa to Medan or vice versa, travelers will be faced with a choice of modes of transportation, namely Mini Bus L300 AC, L300 Non-AC, Jumbo, and Taxi public transport. To determine the choice of this type of transportation, travelers consider various factors, such as travel time, security, comfort, cost, and so on. A large number of choices of transportation modes makes travelers faced with the problem of selection, travelers must consider the interactions between several modes. The purpose of this study was to find out the best mode of transportation chosen by Langsa-Medan travelers and to find out the criteria for the most influential reasons travelers chose in choosing a mode of transportation. The survey was conducted by distributing questionnaires to users of the Mini Bus L300 AC, L300 Non AC, Jumbo, and Taxi modes of transportation, then the survey results were processed using the Analytical Hierarchy Process (AHP) method to determine the weight or optimal value of each mode of transportation for the Langsa- Medan. From the results of the analysis of the Analytical Hierarchy Process (AHP) method, the percentage of influencing factors is obtained, namely Security with a priority weight of 32%, Convenience at 29%, Convenience at 14%, Headway at 11%, Cost 7%, Travel time 7%. While the best mode of traveling Langsa-Medan based on existing criteria is the Mini Bus Jumbo mode of transportation with a priority weight of 36%, L300 AC 23%, L300 Non AC 22%, and Taxi 19%.